Proposition of a teaching game about procariontes for the final years of Fundamental Education (Research, Society and Development, 2020)
Didactic games are instruments that can help teachers in the teaching and learning process in the classroom, since they are tools they have as one of their objectives to make the content presented more attractive to students. Among the complexity of themes in science to be approached in a playful way, is the theme about prokaryotic microorganisms, since in addition to being a complex content is necessary for the visualization of their laboratory structures. The prokaryotic microorganisms are living beings that have as a remarkable characteristic the absence of a nuclear envelope, delimiting the genetic material being representative of this denomination the bacteria and archaeobacteria. In view of the above, didactic games are playful tools that can be used in the teaching of prokaryotes. Thus, the proposition of a didactic game to science teachers in the final years of elementary school, about the prokaryotes worked in that school year is a possibility of diversified methodology that teachers can use in their classes The game presented here was based on the contents related to bacteria and archeobacteria covered in the seventh year of the final years of elementary school. The game called “Procarionte Profile” was built on a PVC board, with low cost material. The game also has cards that deal with issues such as diseases and prophylaxis, ecology and biotechnology, in addition to curiosities about microorganisms. The work showed that, given the complexity of the archeobacteria theme, the board game allowed to explore the content in question without using a microscope or laboratory equipment.